2021
DOI: 10.18280/isi.260310
|View full text |Cite
|
Sign up to set email alerts
|

A Tabu Search Algorithm for General Threshold Visual Cryptography Schemes

Abstract: In Visual Cryptography Schemes (VCSs), for message n transparencies are generated, such that the original message is visible if any k of them are stacked. VCS especially for large values of k and n, the pixel expansion’s reduction and enhancement of the recovered images’ display quality continue to be critical issues. In addition to this, it is challenging to develop a practical and systematic approach to threshold VCSs. An optimization-based pixel-expansion-free threshold VCSs approach has been proposed for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…In order to increase the security of secret files, Rao et al proposed an image encryption method using pixel expansion threshold, and used Tabu search to improve this method. Results showed that this algorithm can effectively solve complex combination problems 12 . Maha• et al proposed a Tabu search with time window to optimize the path at different time points in urban tourism in order to improve the vehicle path planning problem in urban tourism road network.…”
Section: Related Workmentioning
confidence: 98%
See 2 more Smart Citations
“…In order to increase the security of secret files, Rao et al proposed an image encryption method using pixel expansion threshold, and used Tabu search to improve this method. Results showed that this algorithm can effectively solve complex combination problems 12 . Maha• et al proposed a Tabu search with time window to optimize the path at different time points in urban tourism in order to improve the vehicle path planning problem in urban tourism road network.…”
Section: Related Workmentioning
confidence: 98%
“…U r is the unit cost of vehicle pickup and reshipment at the railway station, U w is the unit cost of vehicle pickup and reshipment at the port, and U d is the unit cost of vehicle pickup and reshipment at the distribution center. In addition to the transportation cost calculation formula, the income calculation formula is also established, as shown in formula (12).…”
Section: Profit Optimal Transportation Scheme Optimization Research U...mentioning
confidence: 99%
See 1 more Smart Citation
“…Primarily, the brain tumors are medically diagnosed. Thus, the algorithms for the automatic segmentation of the images applied to computerized tomography (CT) scan [1], positron emission tomography (PET) scan [2,3] and magnetic resonance imaging (MRI) [4][5][6][7][8][9][10][11][12] for segmenting the images of the brain tumors from the images of CT, PET and MRI, respectively. There are preprocessing and post processing developments.…”
Section: Introductionmentioning
confidence: 99%